Sistem harta intelek: peranan dan implikasinya ke atas institusi penyelidikan dan pembangunan (R&D) - Kamal Halili Hassan, (Fakulti Undang - Undang, 2002)

(untitled)
This article seeks to discuss and analyze the role and impact of the intellectual property system on R & D institutions in Malaysia. Over the years, these institutions have successfully innovated various projects that possess intangible value and in fact some of the projects have later on gained greater economic value. Thus, it is of concern to the institutions as well as the researchers to have the innovated projects protected by law. This is where the intellectual property system comes into play in ensuring the rights of the institutions and the obligations of their employees. Areas of intellectual property system that are covered in this article are Copyright Act, Paten Act and confidential information under Common Law. Policy of intellectual property system of Universiti Kebangsaan Malaysia is also discussed as a case study. This article seeks to explain the relevant law, and in such respect the author refers to statutes and cases as decided by the courts